Two theorems on imbeddings of 0-dimensional groups - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In the class of 0-dimensional groups with infinite weight, the universal group is constructed. We prove that a 0-dimensional group can be imbedded into a multiplicative subgroup of a topological ring.